The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010428317701630
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the expression of MGMT and RUNX3 due to non-CpG promoter methylation and their correlation with different risk factors in esophageal cancer patients

Abstract: Promoter methylation reflects in the inactivation of different genes like O 6 -methylguanine-DNA methyltransferase DNA repair gene and runt-related transcription factor 3, a known tumor suppressor gene in various cancers such as esophageal cancer. The promoter methylation was evaluated for O 6 -methylguanine-DNA methyltransferase and runtrelated transcription factor 3 in CpG, CHH, and CHG context (where H is A, T, or C) by next-generation sequencing. The methylation status was correlated with quantitative mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The gene expression level of Runx3 is controlled by promoters that are rich in CpG islands. Previous studies have reported that methylation of promoter regions results in silencing of Runx3 gene expression, which leads to the development of several diseases (49)(50)(51). The present study showed that the protein and mRNA levels of Runx3 were significantly decreased in the PM2.5 and OVA exposure groups.…”
Section: Discussionsupporting
confidence: 62%
“…The gene expression level of Runx3 is controlled by promoters that are rich in CpG islands. Previous studies have reported that methylation of promoter regions results in silencing of Runx3 gene expression, which leads to the development of several diseases (49)(50)(51). The present study showed that the protein and mRNA levels of Runx3 were significantly decreased in the PM2.5 and OVA exposure groups.…”
Section: Discussionsupporting
confidence: 62%
“…RUNX3 is known to have tumor suppressive role in gastrointestinal cancers [ 17 , 43 ]. Studies have shown low level of RUNX3 expression in esophageal tumor samples and its expression has been associated with radio-resistance and poor prognosis [ 33 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CpG sites (numbers 39–49) were covered by less than 10 trimmed reads in at least one tumor or normal tissue sample and therefore were excluded from the analysis. Non-CpG promoter methylation was recently reported to be a key factor in downregulation of some tumor suppressor genes, e.g., O6-methylguanine-DNA methyltransferase gene and runt-related transcription factor 3 ( Saikia et al, 2017 ). This type of modification is unlikely involved in regulation of ALDH1L1 gene in BC since we failed to determine any hypermethylation of non-CpG sites.…”
Section: Resultsmentioning
confidence: 99%